Analisis Pendapatan Usahatani Padi Sawah Secara Mekanik di Desa Puwehuko Kecamatan Mowila Kabupaten Konawe Selatan - Salwia, Salwia; Dirgantoro, Muhammad Arief; Rosmawaty, Rosmawaty (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to determine the level of income of mechanically rice farming in Puwehuko Village, Mowila District, South Konawe Regency, by analyzing significant income between revenues, and costs and the efficiency level of mechanically rice farming in Puwehuko Village, Mowila District, South Konawe Regency. Determination of the study area was carried out by simple random sampling which was used to select 32 rice paddy farmers mechanically. Data were analyzed using analysis of income I = TR-TC and the feasibility of rice farming R / C ratio. The results of this study obtained the average total income of rice farming mechanically in Puwehuko Village, Mowila District, South Konawe Regency, amounting to Rp.5.569.154,30 / planting season with a total average cost of Rp.8.649.595,70 with level of acceptance Rp. 14.218.750 The level of income efficiency of mechanically rice farming in Puwehuko Village, Mowila District, South Konawe Regency shows that the results of R / C ratio of mechanically rice farming is 1.62 which means it is feasible.